Partial Functional Correspondence - Rodola, Emanuele; Cosmo, Luca; Bronstein, M. M.; Torsello, Andrea; Cremers, D. (Computer Graphics Forum, 2017)
In this paper, we propose a method for computing partial functional correspondence between non-rigid shapes. We use perturbation analysis to show how removal of shape parts changes the Laplace–Beltrami eigenfunctions, and exploit it as a prior on the spectral representation of the correspondence. Corresponding parts are optimization variables in our problem and are used to weight the functional correspondence; we are looking for the largest and most regular (in the Mumford–Shah sense) parts that minimize correspondence distortion. We show that our approach can cope with very challenging correspondence settings.
CRIS-Team Scopus Importer:2023-03-08
Keywords: functional maps; I.3.5 [Computational Graphics]: Computational Geometry and Object Modelling-Shape Analysis; partial similarity; shape matching